Ibuprofen arginine for pain control during scaling and root planing: a randomized, triple-blind trial - Dominik A. Ettlin (journal of clinical periodontology, 2006)
Objectives: The aim of this controlled clinical trial was to investigate the analgesic efficacy and tolerability of ibuprofen arginine in patients with mild-to-moderate periodontitis during and after non-surgical periodontal treatment. Methods: This randomized, triple-blind, placebo-controlled, parallel-group trial assessed the analgesic efficacy of ibuprofen arginine (Spedifen s ) in patients undergoing routine periodontal scaling and root planing. 64 patients with chronic periodontitis received either 800 mg ibuprofen arginine or placebo 30 min. before treatment. Numeric pain and electronic visual analogue scales ranging from 0 to 100 were used. Results: The average pain levels during treatment were lower following ibuprofen arginine (quartiles: 0.5, 4.5, 11) compared with placebo (4, 16, 26), corresponding to a percentage reduction in median pain of 72% (p50.023). The median maximum pain was 28 (inter-quartile range 10–50) following placebo and 10 (4–31) following ibuprofen arginine (p50.065). Conclusions: In patients with mild-to-moderate chronic periodontitis, ibuprofen arginine was safe and superior to placebo for alleviating pain during non-surgical periodontal treatment. Its painless administration and rapid onset of action make it well suitable for pain management in a general dental office.